(untitled) (Revista de Ciências Agroveterinárias, 2016)
Micropropagation is a technique widely known for its ability to produce large numbers of plants in a short period of time. It is essential for breeding programs and to establish micropropagation protocols for economically important species. The aim of this study was to establish a micropropagation protocol for quince BA29, aiming at mass production of plantlets. The explants of quince BA29 were cultured on MS and WPM media (original and 1/2) in combination with BAP (0, 0.5, 1, 2 and 4 mg L-1) for the in vitro multiplication and cultured in MS medium with sucrose (15 and 30 mg.L-1) combined with IBA (0, 0.12, 0.25, 0.50, 1.0 and 2.0 mg L-1) for in vitro rooting. After 45 days, the culture media which provided the best results for growth and multiplication of BA29 explants was the MS original with 2.68 mg L-1 of BAP and the culture media which provided the best results for rooting of BA29 explants was MS with 15 g L-1 of sucrose and 1.25 mg L-1 of IBA.